(untitled) (Eurasian Research Bulletin, 2023)
To date, no effective antiviral treatment for coronavirus infection has been developed. The main factor aggravating the condition of patients is developing respiratory failure, with which patients are transferred to the intensive care unit. The fate of patients in the intensive care unit is determined by the extent to which respiratory therapy is performed. Although coronavirus infection is associated with organ failure, so polyorganic insufficiency, respiratory failure is the predominant and crucial factor. With this in mind, the development of optimal options for respiratory therapy and its introduction into intensive care is a topical issue today. The medical mindset of the world has gained a great deal of experience in the use of oxygen therapy, high-flow oxygen therapy (HFOT), noninvasive pulmonary ventilation (NIPV) and invasive pulmonary ventilation (IPV) in patients through the nasal tube. Below we will try to illustrate the selection of an effective method of respiratory therapy based on respiratory indications